Interpolation Algorithm for Fast Evaluation of EM Coupling between Wires - Marasini, C.; Lepelaars, E. S. A. M.; Zwamborn, P. A. M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
Efficient and accurate evaluation of the EM field radiated by a current flowing along a wire is essential to solve the electromagnetic coupling between arbitrary oriented wires. In this paper, a numerically efficient algorithm for the evaluation of coupling is presented. The currents along the wires are expressed in terms of local basis functions. The coupling between each two expansion functions of different wires, using an exact kernel and the Galerkin Method of Moments, requires an integration over the mantle of the radiating element and an integration over the mantle of the receiving element. The computational cost for this 2 × 2D integration is reduced by an interpolation technique. In order to reduce the number of evaluation points and to control accuracy, the interpolation technique is applied to a function that represents the difference between the electric field radiated by a wire element and the analytically known point dipole field. The proposed algorithm is implemented using already available standard routines.